Kesiapan Manajemen Sekolah dalam Pembelajaran Deep Learning di SD Muhammadiyah 1 Ngaglik Sleman - Nur Rohmah Ahsantia; Rahmat Mulyono; Saryanto (Universitas Pakuan, 2026)
School Management's Readiness in Deep Learning at SD Muhammadiyah 1 Ngaglik Sleman The implementation of Deep Learning in elementary schools requires management readiness so that learning innovations can take place effectively and sustainably. This study aims to analyze the readiness of the management of SD Muhammadiyah 1 Ngaglik, Sleman, in implementing Deep Learning. The research uses a descriptive qualitative approach. Data were obtained through semi-structured interviews with one principal, one deputy principal for curriculum, and three classroom teachers, as well as observation and documentation; The validity of the data is strengthened through triangulation and member checking. The results of the study show that school management has a good understanding and commitment to learning innovation. However, implementation readiness is still in the early stages because special training for teachers is still limited, the use of infrastructure and supporting technology is not optimal, and there is no strategic policy document that explicitly regulates the implementation of Deep Learning. These findings imply the need to strengthen teacher capacity, optimize supporting facilities, and prepare a systematic implementation strategy so that the implementation of Deep Learning is more targeted and sustainable.